THE DEVELOPING LIBYAN MARKET - الانصاري للدكتور على (Dirasat in Economics and Business, 1966)
This article tries to explore the trends of the developing Lih market since the start of the oil industry and since the exportati petroleum in the last quarter of 1961. Certain landmarks stand out indicators for the near future. The introduction deals with the duality of the Libyan economy that was existing in the country before the recent boom. A majority os population led a simple life depending essentially on a subsistence level of food, clothing and housing; and enjoying very limited knowledge of twentieth century technology. The other sector of the economy belonged to a minority of foreigners or natives who lived in modern villas, alone brightly lit streets ; possessed cars ; and frequented supermarkets restaurants, hotels and cinemas.